BEBERAPA MASALAH PADA PERJANJIAN KERJA WAKTU TERTENTU DAN SOLUSINYA - -, SUNARNO (Wacana Hukum, 2009)
Abstract: There are two work agreement stated in UU No 13 2003 about labour. They are given-time work agreement and not-given time work agreement. Business people prefer to take the first  for practical reason when they intend to break ther work agreement. That is why government establish rules to protect he labours. However, there ar still some disobedience. Therefore, government still ned to find th solution. Keywords: some problems in given-time work agreement